Ischemic preconditioning vs adenosine vs prostaglandin E1 for protection against liver ischemia/reperfusion injury - Radojkovic,M. (2017)
Ischemia/reperfusion injury is still a major cause of morbidity and mortality during liver surgery and transplantation. A variety of surgical and pharmacological therapeutic strategies have been investigated to minimize the effects of ischemia/reperfusion. The aim of our study was to analyze and compare preventive influences of ischemic preconditioning, adenosine and prostaglandin E1 in the experimental model of hepatic ischemia/reperfusion injury. Adult chinchilla rabbits were divided into four groups: 10 rabbits subjected to liver ischemic preconditioning (3-min period of inflow occlusion followed by a 5-min period of reperfusion) followed by 45 min of Pringle maneuver; 10 rabbits subjected to pre-treatment with intraportal injection of adenosine followed by 45 min of Pringle maneuver; 10 rabbits subjected to pre-treatment with intraportal injection of prostaglandin E1 followed by 45 min of Pringle maneuver; and control group of 10 rabbits subjected to 45 min of inflow liver ischemia without any preconditioning. On the second postoperative day, blood samples were obtained and biochemical parameters of liver function were measured and compared. Liver tissue samples were also obtained and histopathological changes were compared. Based on biochemical and histopathological parameters, it was demonstrated that ischemic preconditioning provided the best protection against hepatic ischemia/reperfusion injury. This was probably due to a wider range of mechanisms of action of this method oriented to reduce oxidative stress and inflammation, and restore liver microcirculation and hepatocyte energy compared to the examined pharmacological strategies.